Bringing Instrumentality In: A Theoretical Case for the Role of Transnational Affiliations in Party-based Europeanisation - Giorgos Charalambous (Journal of Contemporary European Research, 2011)
This article seeks to contribute to the study of party-based Europeanisation. More specifically, I explore, effectively in a theoretical manner, a new avenue of research in the study of the impact of European integration on national political parties, by focusing on the potential role of parties’ transnational affiliations. I do so in an attempt to eliminate or decrease existing theoretical ambiguities and deficiencies that can be thought to lead to a narrow conceptual and empirical focus, when it comes to research on this subject. This narrowness is owed to the omission, by the extant literature, of the potential instrumentality of transnational affiliations in changing, adjusting or reconfirming national political parties' ideological profiles. By extending discussions of party-based Europeanisation, through incorporating the extant argument about instrumentality into the analysis of parties’ transnational affiliations, I illustrate that the spectrum of the impact of European integration on national political parties can be wider than conceded so far.